A method for identifying the important node in multi-layer logistic networks - Wang, Chengwang; Xia, Yongxiang; Zhu, Lingzhe (Frontiers in Physics, 2022)
Traditional methods to identify the important nodes are suitable for single networks. However, many real-world networks are coupled together, which can be modeled by multi-layer networks. Therefore, traditional identification methods may not be suitable for multi-layer networks. In this paper, we propose a new method to identify the important nodes in multi-layer logistic network. Considering the dynamic of the network, a new routing strategy based on the greedy algorithm and iterative method is proposed. The traditional betweenness centrality and closeness centrality are modified according to the new routing strategy to show the traffic condition and topology characteristics of each node. Then the new identification method is proposed based on the modified betweenness and closeness. The new method is compared with some traditional ones, and the simulation results show its advantages.